Peningkatan Keterampilan Menulis Puisi Melalui Media Kumpulan Film Pendek Bertema Pandemi Pada Siswa Kelas 1 Sma Negeri 1 Krian Sidoarjo - Firismanda, M.A. Haris (Inovasi: Jurnal Diklat Keagamaan, 2021)
ABSTRACT This study aimed to improve students’ ability in writing poetry through the medium of short film collection with a pandemic theme. The subjects of this study were the First grade students of SMA Negeri 1 Krian. The results showed that the poetry writing skills of the First grade students of SMA Negeri 1 Krian, Sidoarjo district, had increased. In preliminary study, it was identified that the students' poetry writing skills reached a complete level of 34.61% and an incomplete level of 65.38%. Then, after conducting two cycles, the first cycle reached the level of completion 42. 30% and the level of incompleteness 57.69%. Meanwhile, the second cycle indicated 76.92% level of completion and 23.07% level of incomplete. In conclusion, learning to write poetry through a collection of short films with the theme of pandemic is helpful for students of language class in SMAN 1 Krian Sidoarjo. It could increase their ability in writing poetry. Thus, the researcher suggest the teacher to choose varied learning media in order to enhance their students’poetry writing skill.